Mathematicians' Reflections on Teaching A Symbiosis with Mathematics Education Theories - Stewart, Sepideh (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book opens the case on collaboration among mathematicians and mathematics educators. The authors of this book provide their research and experience based insights on collaboration to inspire the young generation of the mathematics community to engage in productive collaborations and exchange of knowledge early in their careers. These valuable collaborations are anticipated to generate innovative research questions that set new and novel paths for mathematics education research with ample possibilities yet to be realized and discovered.
Chapter 1. Reflecting on teaching mathematics at university: Collaboration among mathematics educators and mathematicians -- Chapter 2. Promoting effective collaboration in the mathematics community -- Chapter 3. Synergy between mathematicians and mathematics educators: Stories of many, and potent, facets -- Chapter 4. Mind the Gap: Reflections on Collaboration in Research and Teaching -- Chapter 5. Students enjoying transformed and improved learning experiences of mathematics in higher education -- Chapter 6. Identifying minimally invasive active classroom activities to be developed in partnership with mathematicians -- Chapter 7. Didactics of Mathematics as a field of mathematical research: the anthropological approach -- Chapter 8. Collaborative evaluation of teaching and assessment interventions: ideas from realistic evaluation -- Chapter 9. The development of inquiry-based mathematics teaching and learning -- Chapter 10. The Intimate Interplay Between Developing Teaching and Exploring Mathematics Through Reflecting in, on, and for, Teaching -- Chapter 11. Signatures of Teaching Mathematics -- Chapter 12. Long-term principles for meaningful teaching and learning of mathematics.
Keywords: Mathematics; Mathematics; History; Education; Teachers -- Training of; Study Skills; Mathematics Education; History of Mathematical Sciences; Education; Teaching and Teacher Education; Study and Learning Skills